Spontaneous Platelet Aggregation in Cerebrovascular Disease II - Hoogenduk, E M G; Jenkins, C S P; van Wijk, E M; Vos, J; ten Cate, J W (Thrombosis and Haemostasis, 1979)
A group of 186 patients with Transient Ischaemic Attacks (TIA) or cerebral Infarction (Cl) was found to demonstrate in vitro Spontaneous Platelet Aggregation (SPA) in 39% of those studied. Of the 176 normal subjects studied the incidence of in vitro SPA was found to be 5%. Further investigation of the phenomenon of SPA revealed that:1. it is associated with ADP-hyperaggregability, i. e. the threshold concentration to induce second wave aggregation is decreased;2. it is dependant on the increase in pH which occurs in platelet-rich plasma stirring in an aggregometer while concurrent ADP-hyperaggregability is independant of this change in pH;3. it is associated with malondialdehyde production and the release of endogenous 5- hydroxytryptamine; and that4. in addition Km and Vmax values for [14C]-5HT incorporation are normal; and that5. no gross abnormalities of the platelet membrane glycoproteins were apparent although occasionally glycoprotein III was found to be increased.This study demonstrates abnormal platelet behaviour in patients with TIA and Cl where the enzyme system involved in thromboxane production is sufficiently stimulated, by stirring alone, to induce aggregation of platelets and the release reaction.Acetylsalicylic acid abolishes SPA and prolongs the bleeding time with similar characteristics as has been described for normal individuals. Plasma (3-thromboglobulin levels are significantly increased in the patients studied. However, no correlation was established with the incidence of in vitro SPA.